Natural Evil and Rebellious Angels: A Critical Evaluation of Gregory Boyd’s Theodicy - McLaughlin, Ryan Patrick (The Evangelical quarterly, 2024)
Gregory Boyd explains the long history of evolution and all suffering that results from it—as well as suffering that results from other natural phenomena—by appealing to an angelic fall through which demonic meddling warps the original, divinely-intended lawlike regularity of the cosmos. With this position, Boyd aims to exonerate God in the face of all evil, which for Boyd includes all forms of suffering. While Boyd’s cosmic warfare theodicy is more thoroughly developed than any other to date and embraces certain scientific evidence about the world in a way that other fall-based theodicies do not, I argue that it nonetheless falls short of a viable theological worldview since it relies upon special pleading and ad hoc premises and ultimately presents an inconsistent system of belief.